The Pattern Of Hadith Usage And Moderate Concepts In Tarekat (A Study of Hadratussyaikh Hasyim Asy'ari's Thoughts in the Book al-Durar al-Muntaṣirah fi Masā’il Al- Tis’a Asyarah) - Alamudin, Muhammad; Husen, Fahmi; Rozaq, Ahmad Shiddiqur; Umam, Fajrul (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2024)
In Sufi literature theory, a wali (saint) generally tends to conceal and hide their spiritual status, as it is considered a trust from Allah SWT that must be safeguarded. However, in recent decades, some individuals have claimed to be walis or even the Imam Mahdi. This phenomenon also occurred during the time of Hadratussyaikh KH. Hasyim Asy'ari, prompting him to respond in his work